PEMBUATAN MINUMAN SERBUK KOPI (Arabica) INSTAN DENGAN PENAMBAHAN EKSTRAK KULIT MANGGIS - Apriani, Fitria Ulfah; Efendi, Raswen '; Rossi, Evy ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to determine and obtain the optimal ratio between extract coffee and extract the mangosteen peel  on its quality of  instant drinks powder. This study used a Completely Randomized Design (CRD) with five treatments and four replications followed by Duncan’s New Multiple Range Test (DNMRT) test at 5%  level. The treatment in this study were K0M0 (rasio extract coffee and extract the mangosteen peel=100: 0), K1M1 (rasio extract coffee and extract the mangosteen peel = 90:10), K2M2 (rasio extract coffee and extract the mangosteen peel = 80:20), K3M3(rasio extract coffee and extract the mangosteen peel = 70:30), and K4M4 (rasio extract coffee and extract the mangosteen peel = 60:40). The results of this study showed that the ratio of extract coffee and extract the mangosteen peel was significantly effected the degrees acidity (pH), content of antioxidants and caffeine, but moisture and ash level were not significant influenced by the treatments. There was also significant effect of treatments on hedonic test for taste, aroma and color of product. The best treatment in this study was K1M1 with moisture, ash and caffeine level respectively 2,18%, 6,30% and 1,72%, pH 5,50, and antioxidants content 33,29 µg/ml. The sensory evaluation  using  hedonic test on flavor, aroma and color of instant drink powder that contain extract coffee and  the mangosteen peel was liked by panelists. Keywords: Extract coffee, extract the mangosteen, and drinks powder coffee instan the mangosteenp peel.